The Effect of Service Quality, Corporate Image and Perceived Value on Customer Loyalty through Customer Satisfaction as a Mediator at the Adventist Hospital in Manado - Walean, Ronny; Ambalao, Shapely; Roring, Marni; Rihi, Marselina Lay (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
The rapid increase in the number of hospitals from year to year compels all hospitals to continually focus on the quality of healthcare. This study is aimed to analyze the structural model of customer loyalty through customer satisfaction as a mediating variable while service quality, corporate image, and perceived value are exogenous variables at the Adventist Hospital in Manado. The study uses a cross-sectional design by utilizing Structural Equation Model (SEM) analysis with SMART PLS. The result of the SMART PLS analysis found that service quality, corporate image, and perceived value have a positive effect on customer satisfaction. Moreover, corporate image and perceived value have significant positive effects on customer loyalty. Whereas service quality does not show a significant effect on customer loyalty as shown on T-statistics to have value <1,96 or p-value >0,05. Customer satisfaction has a significant positive effect on customer loyalty. Furthermore, the results of customer satisfaction are partially mediated by customer satisfaction on customer loyalty. It is recommended that the management of the Adventist Hospital give attention to customer satisfaction as it has been proven to give complete mediating influence to service quality and customer quality, whereas perceived value and the corporate image showed partial influence on customer loyalty. Based on the results, there remains 30,7% of other variables that have not been included in this study and therefore recommended to be accommodated in a future study. Keywords : Service quality, corporate image, perceived value, customer satisfaction, customer loyalty, hospital